Comparative Analysis of Gut Microbiota Between Healthy and Diarrheic Horses - Li, Yaonan; Lan, Yanfang; Zhang, Shuang; Wang, Xiaoli (Frontiers in Veterinary Science, 2022)
Increasing evidence reveals the importance of gut microbiota in animals for regulating intestinal homeostasis, metabolism, and host health. The gut microbial community has been reported to be closely related to many diseases, but information regarding diarrheic influence on gut microbiota in horses remains scarce. This study investigated and compared gut microbial changes in horses during diarrhea. The results showed that the alpha diversity of gut microbiota in diarrheic horses decreased observably, accompanied by obvious shifts in taxonomic compositions. The dominant bacterial phyla (Firmicutes, Bacteroidetes, Spirochaetes, and Kiritimatiellaeota) and genera (uncultured_bacterium_f_Lachnospiraceae, uncultured_bacterium_f_p-251-o5, Lachnospiraceae_AC2044_group, and Treponema_2) in the healthy and diarrheic horses were same regardless of health status but different in abundances. Compared with the healthy horses, the relative abundances of Planctomycetes, Tenericutes, Firmicutes, Patescibacteria, and Proteobacteria in the diarrheic horses were observably decreased, whereas Bacteroidetes, Verrucomicrobia, and Fibrobacteres were dramatically increased. Moreover, diarrhea also resulted in a significant reduction in the proportions of 31 genera and a significant increase in the proportions of 14 genera. Taken together, this study demonstrated that the gut bacterial diversity and abundance of horses changed significantly during diarrhea. Additionally, these findings also demonstrated that the dysbiosis of gut microbiota may be an important driving factor of diarrhea in horses.